RELATIONSHIP BETWEEN NITRIC OXIDE ACCUMULATION, ANTI-OXIDATIVE SYSTEM AND FREEZING TOLERANCE IN THE LEAVES OF SABINA DURING COLD ADAPTATION - Y. P. Chen; J. Zhang; Z. J. Yang; F. Yu; Y. Q. Li (Journal of Animal and Plant Sciences, 2012)
Signal function of endogenous nitric oxide (NO) and freezing-resistant traits in the leaves of Sabina przewalskii Kom. (SP) and Sabina chinensis (Lin.) Ant. (SC) during cold acclimation and freezing tolerance were investigated. The results indicated that with the decrease in temperature electrolyte leakage (EL) and thiobarbituric acid-reactive substances (TBARS) content increased markedly and reached two peaks in September and February, ratio of free water content (FWC) to bound water content (BWC) decreased and the lowest value was found in the winter (during November to January). Both NO and the anti-oxidative systems played an important role in potentiating freezing-resistance and limiting the production of free radicals to protect membrane integrity. Activities of catalase (CAT), perixidease (POD) and ascorbate peroxidase (APX), contents of ascorbic acid (ASA), glutathione (GSH), proline (Pro) and carotenoid (Car) increased with temperature decrease, and highest in the winter, the rate of NO release, NO synthase (NOS) and nitrate reductase (NR) activity increased markedly and reached two peaks respectively in September and February. Meanwhile, the increment of NO generation is always found before decreasing of the ratio of FWC to BWC and increasing of anti-oxidative enzyme activity and antioxidant content. It indicated that NO as an early signal molecule is able to induce the freezing tolerance by increasing the content of bound-water in cell and activating the anti-oxidative system.
Keywords: Sabina; anti-oxidative system; nitric oxide; freezing tolerance.